Nonpuerperal inversion of uterus secondary to leiomyoma in menopause: a rare case report - E., Kalarani; P., Amudha; M., Rubini; A., Karthika Devi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Inversion of uterus is a rare clinical condition if not associated with third stage of labor or puerperium. Non-puerperal uterine inversion usually occurs secondary to tumor arising from the fundus of uterus. We report an unusual case of non-puerperal uterine inversion caused by large submucous fibroid in a 65 year old postmenopausal woman which was managed by combined abdomino-perineal approach.